Analisis Kelayakan Usaha Lemang di Kota Tebing Tinggi - Tampubolon, Pentagon; Manik, Pretty Wati; Damanik, Rapika Kesatriani; Malau, Tresiawati (Asosiasi Dosen Akuntansi Indonesia, 2024)
The purpose of this study is to analyze the availability of production inputs and feasibility studies of lemang businesses whether they are feasible to be developed in Tebing Tinggi City. The research method in determining the location of the study was purposive, namely Tebing Tinggi City. Population sampling used the census method, namely taking all samples in the research area, namely 17 lemang entrepreneurs. Sampling was carried out using Random Sampling and a sample of one lemang business in Tebing Tinggi City was obtained. Data collection methods consist of secondary data and primary data. The data analysis method used is the descriptive method, feasibility analysis and sensitivity analysis. The results of the study obtained from this study are, production inputs that are specifically for labor and capital are available in the research area, the results of the study show that R / C > 1, BEP production volume <from the production produced, BEP price <production price which means that the lemang business is feasible to be run, and the sensitivity of the lemang business is at 18-23%, namely when all production costs are increased by 18-23% the lemang business is still feasible to be developed